Combating Micronutrient Deficiencies: Food-Based Approaches 2010
DOI: 10.1079/9781845937140.0137
|View full text |Cite
|
Sign up to set email alerts
|

Small-animal revolving funds: an innovative programming model to increase access to and consumption of animal-source foods by rural households in Malawi.

Abstract: Increased intake of animal-source foods is a key means to improve nutritional status in populations with high levels of nutrient deficiencies. However, there are few examples of programming models that have successfully improved both access to and consumption of animal products in resource-poor settings. This chapter presents a case study of a community-based intervention to increase household access to and consumption of animal-source foods, implemented as part of a comprehensive, 9-year nutrition and health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Indeed, there is some evidence that livestock programs can result in increased income 7 -13 and increased consumption of animal source foods. 8,9,14 -21 However, one or both of these benefits were not realized in other programs, 10,12,14,22 -25 and scientifically rigorous evidence for improvement in household welfare via women’s empowerment is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is some evidence that livestock programs can result in increased income 7 -13 and increased consumption of animal source foods. 8,9,14 -21 However, one or both of these benefits were not realized in other programs, 10,12,14,22 -25 and scientifically rigorous evidence for improvement in household welfare via women’s empowerment is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies had multiple outcomes. For the nutritional outcomes measured, dietary diversity was reported by 9% ( n = 5) of the studies ( 46 50 ), consumption of ASFs by 18% ( n = 10) of the studies ( 27 , 46 , 50 57 ), hemoglobin concentration and prevalence of anemia by 7% ( n = 4) of the studies ( 51 , 58 60 ), stunting or HAZ z-scores by 33% ( n = 18) of the studies ( 27 , 46 48 , 51 53 , 55 57 , 61 68 ), wasting or WHZ z-scores by 15% ( n = 8) of the studies ( 27 , 46 , 47 , 51 , 55 57 , 61 ), and 18% ( n = 10) reported on underweight or WAZ z-scores ( 27 , 46 48 , 53 , 60 , 61 , 68 70 ) Based on study design, of the 29 studies reviewed, 14% ( n = 4) were livestock oriented impact evaluations, 4% ( n = 1) evaluated dairy sensitive value chains, 41% ( n = 12) were observational studies, and 41% ( n = 12) were experimental studies ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, their review is different from ours because the former focused on general agriculture interventions including homestead food production systems, home vegetable gardens, biofortified crops, livestock, and irrigation projects and their effect on nutrition in the general population. Our review focused mainly on livestock-oriented interventions and their effect on nutrition in children under 5 years old and/or pregnant and lactating women specifically in Africa.Based on our evidence synthesis, a sizeable percentage of articles showed that livestock interventions improved access to and consumption of nutrient-dense animal-source foods (27, 46, 50-57), attaining minimum dietary diversity (46-50), hemoglobin concentration, and prevalence of anemia(51,(58)(59)(60).Additionally, some livestock interventions improved children's stunting or height-for-age (HAZ) z-scores (27, 46-48, 51-53, 55-57, 61-68), wasting or weight-for-height (WHZ) z-scores (27, 46, 47, 51, 55-57, 61), and underweight or weight-for-age (WAZ) z-scores(48,61,68,69), which are indicators of chronic and acute nutritional status in children. This positive effect is because livestock and livestock products are a source of essential, nutrient-dense, and highly bioavailable ASFs and are a source of household income through sales of livestock and livestock products, which translates to improved nutritional status among women and children in underserved and vulnerable populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That relationship is mediated by food access, health and caring practices [1][2][3][4][5]. This paper helps to make clear that improvements in agriculture can lead to positive nutritional outcomes if these other mediating factors are in place.…”
mentioning
confidence: 99%